Applied writing for technicians - Jungk, Dale (McGraw-Hill, 2005)
Applied Writing for Technicians is a text-workbook intended for use in writing courses for students in technology programs. Using the writing process, students studying various technical fields from electronics, to HVAC to medical office, to computer networking will develop their written communication skills while creating job-related correspondence. Coverage includes both internal and external job-related correspondence such as proposals for expenditure, and job bids as well as routine information requests and detailed billing reports. Standard conventions and formats for letters, memos, e-mail, and other reports are also covered. This versatile text is intended for use both in classes where students are studying various technical fields, and in classes where all of the students share a common major.